A novel IRF6 mutation causing non-syndromic cleft lip with or without cleft palate in a pedigree. (20th July 2018) - Zhao, Huaxiang; Zhang, Mengqi; Zhong, Wenjie; Zhang, Jieni; Huang, Wenbin; Zhang, Yunfan; Li, Weiran; Jia, Peizeng; Zhang, Taowen; Liu, Zhonghao; Lin, Jiuxiang; Chen, Feng
Abstract: Non-syndromic cleft lip with or without cleft palate (NSCLP) is the most common congenital craniofacial malformation, and its harmful influence on affected individuals is apparent. Despite many studies, the causative genes and their mechanisms are not completely clear. We recruited a Han Chinese NSCLP family and explored the causative variant in this pedigree. We performed whole-exome sequencing on two patients. Bioinformatics screening and analysis were used to identify the mutation. We also performed species conservation analysis, mutation function predictions, and homology protein modelling to evaluate the influence of the mutation. We identified a rare mutation in interferon regulatory factor 6 (IRF6) (c.26G>A; p.Arg9Gln) as a candidate of causative mutation. This mutation was predicted to be deleterious. The codon is conserved in many species. The residue change caused by this mutation would affect the structure of IRF6 to a degree. Our study suggested that the rare IRF6 variant is probably the pathogenic mutation in this family. Our result adds evidence that IRF6 variants play a role in the aetiology of orofacial clefts.